Formal Informality : Informal Practices of Formal Firms as a Key Business Constraint - World Bank Group (World Bank, Washington, DC, 2017)
Despite strong economic growth in recent decades led by the resource-based sectors, Lao PDR facessignificant challenges, including high poverty rates and limited productivity. A highly challenging business and investment environment continues to hamper stronger private sector-led growth, especially outside the natural resource sectors, where job creation could be larger. In the still largely unreformed business and trade environment, the World Bank’s 2016 Enterprise Survey identified "practices of firms in the informal sector" as the biggest problem reported by firms in the country, and addressing these and other challenges fundamentally will be critical to generate inclusive growth. Based on interviews with business owners and top managers, this note finds that there are four main types of problematic informality in Lao PDR’s business environment: inadequately registered enterprises that "fly under the radar"; widespread tax evasion; irregular adherence to complex and burdensome regulations; and a culture of noncompliance with basic rules and standards. Fully registered and formalized firms incur higher costs and feel unfairly targeted by authorities who are eager to collect revenue and fulfil their mandates. Unregistered or rule-evading competitors are alleged to escape the same level of scrutiny, due to the difficulty of enforcement and prevalence of petty corruption. Tackling problematic informality in the business environment will require stronger institutions and a continued government focus on eliminating petty corruption. In the near-term, this note recommends eliminating unnecessary regulations and streamlining others by leveraging public support for transparency and consistency in the tax and regulatory systems. This should be complemented by a functional, efficient one stop window for enterprise registration to encourage formalization. Putting these recommendations into practice will require improved monitoring, evaluation, and assessment practices based on reliable and timely common data.